Psychiatric advance directives facilitated by peer workers among people with mental illness: economic evaluation of a randomized controlled trial (DAiP study) - S. Loubière; A. Loundou; P. Auquier; A. Tinland (Cambridge University Press, 2023)
Abstract Aims We aimed to assess the cost-effectiveness of psychiatric advance directives (PAD) facilitated by peer workers (PW-PAD) in the management of patients with mental disorders in France. Methods In a prospective multicentre randomized controlled trial, we randomly assigned adults with a Diagnostic and Statistical Manual of Mental Disorders, fifth edition diagnosis of schizophrenia, bipolar I disorder or schizoaffective disorders, who were compulsorily hospitalized in the past 12 months, to either fill out a PAD form and meet a peer worker for facilitation or receive usual care. We assessed differences in societal costs in euros (€) and quality-adjusted life-years (QALYs) over a year-long follow-up to estimate the incremental cost-effectiveness ratio of the PW-PAD strategy. We conducted multiple sensitivity analyses to assess the robustness of our results. Results Among the 394 randomized participants, 196 were assigned to the PW-PAD group and 198 to the control group. Psychiatric inpatient costs were lower in the PW-PAD group than the control group (relative risk, −0.22; 95% confidence interval, [−0.33 to −0.11]; P < 0.001), and 1-year cumulative savings were obtained for the PW-PAD group (mean difference, −€4,286 [−4,711 to −4,020]). Twelve months after PW-PAD implementation, we observed improved health utilities (difference, 0.040 [0.003-0.077]; P = 0.032). Three deaths occurred. QALYs were higher in the PW-PAD group (difference, 0.045 [0.040-0.046]). In all sensitivity analyses, taking into account sampling uncertainty and unit variable variation, PW-PAD was likely to remain a cost-effective use of resources. Conclusion PW-PAD was strictly dominant, that is, less expensive and more effective compared with usual care for people living with mental illness.